Advanced interfacing techniques for sensors : measurement circuits and systems for intelligent sensors - George, Boby (Springer, 2017)
This book presents ways of interfacing sensors to the digital world, and discusses the marriage between sensor systems and the IoT: the opportunities and challenges. As is often affected by noise and interference, the book presents effective schemes for recovering the data from a signal that is buried in noise. It also explores interesting applications in the area of health care, un-obstructive monitoring and the electronic nose and tongue. It is a valuable resource for engineers and scientists in the area of sensors and interfacing wanting to update their knowledge of the latest developments in the field and learn more about sensing applications and challenges.
Keywords: Intelligent sensors.; Internet of things.; elektronické knihy; electronic books